Course of upper eyelid retraction in thyroid eye disease. Issue 2 (11th May 2019) - Lee, Dong Cheol; Young, Stephanie M; Kim, Yoon-Duck; Woo, Kyung In
Abstract : Aims: To evaluate the natural course of upper eyelid retraction (UER) in patients with thyroid eye disease (TED) and factors affecting its course. Methods: Retrospective non-interventional cohort study in a single tertiary institution from March 2006 to March 2015 on patients with TED with (1) unilateral or bilateral UER within 6 months from initial presentation, and (2) no prior interventions nor surgical treatment for their UER. Main outcomes and measures were mean margin reflex distance 1 (MRD1) and factors associated with UER improvement. Results: There were a total of 61 patients and 81 eyes (41 unilateral and 20 bilateral UER). Mean age was 42.3±15.1 years. Mean MRD1 decreased from 6.1 mm at presentation to 4.8 mm at 12 months, and 4.4 mm at 24 months. The proportion of eyes with normalisation of lid height increased from 0% at presentation to 22.2% at 6 months, 37.0% at 12 months and 49.4% at 24 months. Mean time to normalisation of MRD1 was 18.0±12.4 months. A positive family history of TED was found to be associated with a 6.2 times lower likelihood of normalisation. Change in exophthalmometry, clinical activity score and thyroid-stimulating immunoglobulin were significantly correlated to change in MRD1 (p<0.05). There was no correlation between change in MRD1 and thyroid-stimulating hormone receptor antibodies. Conclusion: An improved knowledge of the natural history of UER in TED will allow us to better decide and evaluate the optimal management for such patients.